MiR-132-3p Modulates MEKK3-Dependent NF-κB and p38/JNK Signaling Pathways to Alleviate Spinal Cord Ischemia-Reperfusion Injury by Hindering M1 Polarization of Macrophages - Fang, Hua; Li, Hua-Feng; Pan, Qin; Jin, Hon-Ling; Yang, Miao; Wang, Ru-Rong; Wang, Quan-Yun; Zhang, Jian-Ping (Frontiers in Cell and Developmental Biology, 2021)
Spinal cord ischemia-reperfusion (SCIR) injury is a serious complication of open surgical and endovascular aortic procedures. MicroRNA-132-3p (miR-132-3p) has been reported to be involved in the progression of various diseases, but its role in SCIR injury is unclear. Thus, we aimed in this study to investigate the mechanism of miR-132-3p in SCIR injury and explore its pathway as a therapeutic target for SCIR injury. We first constructed a SCIR injury rat model and documented motor function in the model. RT-qPCR and Western blot analysis were used to detect the expression of miR-132-3p and mitogen-activated protein kinase kinase kinase 3 (MEKK3) in SCIR injury rats. The interaction between miR-132-3p and MEKK3 was identified by dual-luciferase reporter gene assay. Then, the effects of miR-132-3p and MEKK3 on macrophage M1 polarization were evaluated in vitro and in vivo by altering their expression in macrophages of SCIR injury rats, with treatments altering the NF-κB and p38/JNK signaling pathways using SP600125, SB203580, or PDTC. The SCIR injury rats had a high Tarlov score and low miR-132-3p expression along with high MEKK3 expression. miR-132-3p could directly bind to MEKK3, and that macrophage M1 polarization and inflammation could be inhibited by overexpression of miR-132-3p through downregulating MEKK3 and inactivating the NF-κB and p38/JNK signaling pathways. Besides, increased miR-132-3p expression could decrease the injured rat Tarlov score. Overall, our study demonstrated that miR-132-3p can suppress M1 polarization of macrophages and alleviate SCIR injury by blocking the MEKK3-dependent activation of the NF-κB and p38/JNK signaling pathway. Thus, miR-132-3p and its downstream pathways may be useful targets to alleviate the symptoms of SCIR injury.